Pelatihan Pembuatan E-Booklet Product Pada UMKM Jamu Ngesti Rempah Semarang - Augustine Graciafernandy, Maria; Rotua Simamora, Elisabeth; Usriyono, Eko (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
Entrepreneurship is one of the factors that strengthens the economic structure of a country. Economic growth in Indonesia is influenced by various factors, one of which is the involvement of MSMEs. Digitalization is an important agenda for MSMEs because digitization itself can help MSMEs to survive amidst the competition for many imported goods entering Indonesia. cheap. In an effort to develop product marketing, it is necessary to master the use of digital marketing so that it can grow/increase enthusiasm and inspiration in running an online-based business, and improve skills in using technology, especially in online marketing. Pre-survey activities have been carried out at the UMKM Ngesti Rempah Semarang. The implementation of this PKM is to conduct training for making e-booklets to promote the products. The goal of this PKM is to provide assistance to MSME Partners in terms of utilizing digital technology to carry out product marketing and increase sales.